Annual patient and caregiver burden of oncology clinic visits for granulocyte-colony stimulating factor therapy in the US. (3rd May 2016) - Stephens, J. Mark; Li, Xiaoyan; Reiner, Maureen; Tzivelekis, Spiros
Abstract: Objective: Prophylactic treatment with granulocyte-colony stimulating factors (G-CSFs) is indicated for chemotherapy patients with a significant risk of febrile neutropenia. This study estimates the annual economic burden on patients and caregivers of clinic visits for prophylactic G-CSF injections in the US. Methods: Annual clinic visits for prophylactic G-CSF injections (all cancers) were estimated from national cancer incidence, chemotherapy treatment and G-CSF utilization data, and G-CSF sales and pricing information. Patient travel times, plus time spent in the clinic, were estimated from patient survey responses collected during a large prospective cohort study (the Prospective Study of the Relationship between Chemotherapy Dose Intensity and Mortality in Early-Stage (I–III) Breast Cancer Patients). Economic models were created to estimate travel costs, patient co-pays and the economic value of time spent by patients and caregivers in G-CSF clinic visits. Results: Estimated total clinic visits for prophylactic G-CSF injections in the US were 1.713 million for 2015. Mean (SD) travel time per visit was 62 (50) min; mean (SD) time in the clinic was 41 (68) min. Total annual time for travel to and from the clinic, plus time at the clinic, is estimated at 4.9 million hours, with patient and caregiver time valued at $91.8 million ($228 per patient). The estimated cumulative annual travel distance for G-CSF visits is 60.2 million miles, with a total transportation cost of $28.9 million ($72 per patient). Estimated patient co-pays were $61.1 million, ∼$36 per visit, $152 per patient. The total yearly economic impact on patients and caregivers is $182 million, ∼$450 per patient. Limitations: Data to support model parameters were limited. Study estimates are sensitive to the assumptions used. Conclusions: The burden of clinic visits for G-CSF therapy is a significant addition to the total economic burden borne by cancer patients and their families.